Analysis of coffee bean supplier selection using AHP-TOPSIS methods: case study on a ready-to-use coffee powder company - Sanjaya, Yahya Cakra; Pulansari, Farida; Rahmawati, Nur (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
The global market competition that companies must face along with increasingly competitive market developments means that each company has its own challenges in preparing competitive strategies. PT. XYZ is a company that operates in the field of coffee bean processing. The related problems that occur are frequent delays in sending raw materials by suppliers which results in delivery delays, which means they are related to supplier selection problems. Therefore, in this research, the AHP TOPSIS method was used to conduct supplier analysis, AHP is utilized to make decisions and consider multiple factors, subsequently ranking them. Meanwhile, TOPSIS is employed to address multi-criteria problems by comparing the best alternative with the worst alternative among many options. The results of this research are that Supplier 4 is in first place with a preference value of 0.6510, while the second and third places are occupied by Supplier 1 and Supplier 3 respectively.